QUALITY IN EDUCATIONAL SERVICE: EXPECTATIONS VERSUS PERFORMANCE IN THE ACCOUNTING UNDERGRADUATE COURSE - Morais Borges, Lara Fabiana; Silva Santos, Cassius Klay; Araujo Leal, Edvalda (European Scientific Journal, ESJ, 2014)
This paper aimed to identify and to analyze the expectations and perceptions of students in Accounting Undergraduate Course concerning to the following characteristics: reliability, care, safety, empathy and tangibility. We applied SERVQUAL instrument. The study was carried out to students of a public College in Minas Gerais State, Brazil. The sample consisted of 189 participants. It is a descriptive search which was conducted as a survey and we analyzed data in a quantitative approach applying statistical tests. The first stage consisted of a descriptive analysis and we further applied the Wilcoxon non parametric test, in order to compare the population means in paired samples (expectations and perceptions / performance). The results showed that, in the analyzed sample, the students have good expectations and perceptions on the Accounting course quality concerning to the analyzed aspects. We observed that, in the analysis of the students in the period in which they are enrolled, the averages were close. We compared the expectations and the perception of course quality, with small change variations to later periods, which indicates that the students of these periods evaluate more positively the course quality. Comparing average differences we stated that all the investigated quality dimensions (reliability, care, safety, empathy and tangibility) were significant at 5% level, which indicates that there is a difference between expectations and perceptions of the analyzed students.